2008
DOI: 10.7202/018090ar
|View full text |Cite
|
Sign up to set email alerts
|

L’enseignement au Québec et en France des questions controversées en histoire : tensions entre politique du passé et politique de la reconnaissance dans les curricula

Abstract: RésuméCet article traite de l’expression des tensions entre la politique du passé et la politique de la reconnaissance dans l’enseignement des questions controversées en histoire au Québec et en France. L’histoire à enseigner y a connu d’importantes évolutions. Ces évolutions concernent la conception même de l’histoire et son rôle dans la société. Elles sont porteuses de tensions quant à ce qui est légitime pour « dire/faire l’histoire », donc à la part de récit commun et de cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Located within memories of often‐unequal inter‐group power relations as well as within larger Franco‐Québécois imperatives of cultural and linguistic renewal, these two variants seemingly represent two options for knowing and acting toward the significant Other that emerge in ongoing debates over how to best capture and transmit Quebec's past in school history classrooms. Undoubtedly, the “openness to the Anglo‐Québécois” choice here corresponds to those discourses that call for producing critically engaged citizens that fundamentally appreciate differing viewpoints of the past for developing personal perspectives of temporal change, whereas the “remembering of past injustices” option instead embodies those concerns of promoting the Franco‐Québécois historical experience (i.e., collective memory) as the only viable collective narrative framework for integrating social diversity (Lévesque, 2004; Bulletin d'Histoire Politique, 2007; Éthier et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Located within memories of often‐unequal inter‐group power relations as well as within larger Franco‐Québécois imperatives of cultural and linguistic renewal, these two variants seemingly represent two options for knowing and acting toward the significant Other that emerge in ongoing debates over how to best capture and transmit Quebec's past in school history classrooms. Undoubtedly, the “openness to the Anglo‐Québécois” choice here corresponds to those discourses that call for producing critically engaged citizens that fundamentally appreciate differing viewpoints of the past for developing personal perspectives of temporal change, whereas the “remembering of past injustices” option instead embodies those concerns of promoting the Franco‐Québécois historical experience (i.e., collective memory) as the only viable collective narrative framework for integrating social diversity (Lévesque, 2004; Bulletin d'Histoire Politique, 2007; Éthier et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the degree of both educators' sensitivity to Anglophone social realities and historical experiences become clear, as do their willingness to transmit such information to their students and their openness to considering the latter as an integral part of a common Quebec collective identity. Given the centrality of the “French–English Conflict” in both educators' workings of historical consciousness, which also underlie general Francophone recollections of the Anglo‐Québécois as well as larger societal debates over Quebec history teaching (Létourneau & Moisan, 2004; Lévesque, 2004; Lemire, McAndrew, & Smith, 2006; Létourneau, 2006; Éthier et al., 2007), this article ends with suggesting a means for fostering autonomous and conscientious engagements with the past in the national history classroom. Not only does such an approach entail respecting differences in opinions and choices among students, but also highlights the potentials of embracing change for improving the quality of common future life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, this is shown in the PFQ's pages (Ministère de l'Éducation du Québec [MÉQ], 2004). Lefrançois & Éthier (2008) showed that in the PFQ's pages there are 247 occurrences of the base word citizen or its derivatives (citizens, citizenship, etc.). Of this number, 43% (105 words) are encountered in the 39 pages devoted to history courses (now called History and Citizenship Education, HCE), not counting 22 (9%) appearing elsewhere in the PFQ, which refers to HCE.…”
Section: Historical Consciousness In Québec 'S History Curriculummentioning
confidence: 99%
“…History is replete with controversial questions and politically sensitive interpretive debates. Historical narratives often extol the emotions of numerous people regarding important issues and complex topics, upon which it is impossible to rule based only on an examination of facts or experience (Berg, Graeffe & Holden, 2003;Éthier, Lantheaume & Lefrançois, 2008;Evans & Saxony, 2007;Wellington, 1986).…”
Section: Introductionmentioning
confidence: 99%